PERAN HUKUM ADAT DALAM PELESTARIAN LINGKUNGAN HIDUP DAERAH - I Nyoman Sirtha (Environmental Research Center (PPLH) of Udayana University)
A traditional law (Adat Law) is one element on construction The Unwritten NationalLaw of Indonesia. On sustainable development which deals with environmental dimention inthe regional frame and in line with the spirit of regional otonomy which implys exploitate(utilize) the natural resources and biological potencies includes norms which is still practiseby the society for the human’s wealth and other creatures.Therefore, Adat Law which is till existing among the societies can play an importantrole to regulate and to constrain the human behaviors in term of environmental conservationin order to realize the harmonious and equal life